THE MIYONKOL OASIS IN THE PAGES OF HISTORY - Sodikovna, Norkulova Gulida (Journal of Learning on History and Social Sciences, 2025)
Objective: This study explores the historical evolution of geographical names in the Miyonkol oasis, a fertile and strategically significant region in the Zarafshan Valley. Despite its rich cultural and economic heritage, the historiography of its naming conventions has remained underexplored. Method: Utilizing a historical-analytical method, the research draws from medieval chronicles, travelers’ narratives, and Russian-era documentation to trace the transformation of toponyms such as Nim Sugd, Sugdi Khurd, and Miyonkol. Results: Findings reveal that the oasis was not only a hub of agriculture and trade during the Turkic Khaganate and the Russian period but also home to important settlements like Ishtikhan and Ofarinkent. The results emphasize the oasis's central role in regional development and identity formation. Novelty: The novelty of this study lies in its focus on the historiographical gap concerning the toponymic evolution of the Miyonkol oasis, an area rich in cultural and economic significance that has not been thoroughly examined through historical and interdisciplinary lenses. The study implies the necessity for further comparative and interdisciplinary research, including digital mapping and archaeological analysis, to fully contextualize Miyonkol’s contribution to Central Asian history. This research reveals the various names used in historical sources to classify the geographical identity of the Miyonkol region. It explores how the area was referred to as Nim Sugd and Sugdi Khurd in ancient times and came to be known as Miyonkol during the medieval period. The study highlights the existence of strategically important areas such as Ofarinkent, Ishtikhan, and Sogarj.